Dielectric response of (Pb0.7Nd0.15Bi0.15)(Fe0.3Ti0.7)O3 material. Issue 2 (March 2021) - Samal, S.K.; Pradhan, S.K.; Mallick, M.K.; Choudhary, R.N.P.; Bhuyan, S.
Abstract: A neodymium (Nd substituted BiFeO3 : BFO and PbTiO3 : PT) binary electronic compound has been developed with the help of solid state oxide-mixing process. The electrical properties, such as dielectric response (relative permittivity & loss tangent), resistive behavior (impedance spectrum) and conductivity, as well as electric modulus of the developed ceramic powder material, have been delineated. The compound entails high dielectric constant with relatively lower loss tangent with increased conductivity which affirmed the material as a potential contender for ferroelectric based electronic device applications.